Extraordinary groups : - Schaefer, Richard T. (Worth, 2008)
extraordinary groups offers the reader an extraordinary view into some of America's most avoidant and little known religions. Several of the groups portrayed by the authors are seldom accessible to the general population. For instance, rarely is there truly a detailed account of the Gypsy movement as striking as the one in this book. Also, for the religious historian the analysis of the Father Divine movement is both intriguing and fascinating, in addition, this is a historical movement that few Afro-Americans are even aware existed. Thanks Zellner for a great read!